FORMULATION OF TRANSDERMAL PATCHES OF MICONAZOLE NITRATE AND ASSESMENT FOR DRUG RELEASE - Nazarkar, Swapnil; Kondawar, Manish; Vedpathak, Prasad; Khedkar, Samrat; Dayama, Dharmesh (International Journal of Current Pharmaceutical Research, 2014)
Adhesive transdermal patches containing Miconazole Nitrate were prepared as an antifungal therapy. Eudragit RS 100 and Eudragit RL 100 were used in combination as matrix polymers. The patches were assessed for release using a model drug as Miconazole Nitrate by diffusion method. Subsequently, the permeation enhancement effect of DMSO and 2-pyrrolidone was studied. The patches have shown significant controlled release property of the model drug which can be used for a prolonged effect of the drug avoiding the first pass deactivation of Miconazole Nitrate. The patches were also evaluated using various parameters as weight variation, tensile strength, moisture uptake, moisture loss, drug content and other significant parameters. Selected formulations were subjected for their ex-vivo studies on rodent skin.